Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA): Labor Management Procedure (LMP) for Mali cluster activities - Africa Rice Center (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This Labor Management Procedures (LMP) has been developed by AfricaRice to guide mitigation and response to project risks relating to working conditions and occupational health and safety (OHS) of workers and community members during the implementation of the Accelerating Impact of CGIAR Climate Research for Africa (AICCRA) project activities in Mali. The purpose of this LMP is to facilitate the identification of different types of workers that are likely to be involved in the project and set out the ways in which those workers will be managed in accordance with the requirements of Mali labor laws and the objectives of the World Bank Environmental and Social Standard 2: Labor and Working Conditions (ESS2). It will cover the whole life of the Project. This LMP is a living document and would be updated as and when the scope of work for AICCRA Mali and its related labor requirements change.